Pengendalian Internal Kas Masjid Berbasis Amanah dan Muraqabah - Firdaus Reffiandra; Venantya Asmandani (Equivalent : Journal of Economic, Accounting and Management, 2024)
Abtract : The aim of this research is to analyze the internal cash control implemented at the Al-Mubarok Mosque, Banyuwangi Regency, based on trust and muraqabah. This research uses a qualitative approach with descriptive methods. Starting with data collection in the form of observations, interviews and documentation. This research technique involves evaluating the implementation of internal control implemented in the Al-Mubarok Mosque and its relationship to the financial management process. The research results show that the mosque management has implemented internal control methods to manage the mosque's finances with trust and muraqabah. Starting with recording the mosque's money or cash to making complex financial reports as a form of accountability to the congregation. Abstrak : Tujuan dari penelitian ini menganalisis pengendalian internal yang diterapkan pada sebuah Masjid Al-Mubarok Kabupaten Banyuwangi berbasis amanah dan muraqabah. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Diawali dengan pengumpulan data berupa observasi, wawancara, dan dokumentasi. Teknik penelitian ini dengan cara mengevaluasi pelaksanaan pengendalian internal yang diterapkan dalam Masjid Al-Mubarok dan keterkaitannya dengan proses pengelolaan keuangan.Hasil penelitian menunjukkan bahwa pengurus masjid telah menerapkan metode pengendalian internal sebagai pengelolaan keuangan masjid dengan amanah dan muraqabah. Dimulai dengan pencatatan uang atau kas masjid hingga membuat laporan keuangan secara kompleks sebagai bentuk pertangguangjawaban kepada para jamaah.